Ultrasensitive sensing of tris(2, 3-dibromopropyl) isocyanurate based on the synergistic effect of amino and hydroxyl groups of a molecularly imprinted poly(o-aminophenol) film. (21st December 2015) - Ma, Xiuling; Liu, Jiaxiang; Wu, Dan; Wang, Lihua; Zhang, Zhangjing; Xiang, Shengchang
Abstract : The ultrasensitive sensing of tris(2, 3-dibromopropyl) isocyanurate was achieved by the synergistic effect of amino and hydroxyl groups in an imprinted poly( o -aminophenol) film. Abstract : A facile approach for sensing an emerging persistent organic pollutant, tris(2, 3-dibromopropyl) isocyanurate (TBC) is developed based on coupling molecularly imprinting with electro-polymerization of o -aminophenol (OAP), which is an electro-active monomer containing multifunctional groups. The poly-OAP film was deposited in an OAP solution by the potentiodynamic cycling of the potential with and without the template (TBC) on a glassy carbon electrode. Using K3 [Fe(CN)6 ] as an electro-active marker, the properties of the TBC imprinted electrode were investigated by electrochemical measurements. The results showed that the sensor with a low detection limit of 6.64 × 10 −11 mol L −1 (S/N = 3) for TBC determination was significantly different from the non-imprinted electrode. By selecting aniline, without a hydroxyl group, as a reference for controlled trials, the limit of detection for the poly-OAP film-coated electrode is ca. 10 times smaller than that of the polyaniline-coated one, and the sensitivity of the poly-OAP film is ca. 2 times higher than that of the polyaniline one. It demonstrates that more binding sites might improve the detection ability of the imprinted sensor.